Antibacterial Activity of Synthesized Graphene Oxide Modified Nickel Phthalocyanine - Saad Abbas Jasim (Journal of Global Pharma Technology, 2016)
The antimicrobial properties of Graphene Oxide Modified Nickle Phthalocyanine were evaluated against Staphylococcus aureus, Gram-positive bacterium and sydomonus, Gram-negative one.. Bacteriological tests were performed in Muller Hinton solid agar plates with different concentrations of graphene oxide particles. The inhibition zones as a function of added graphene oxide where studied ,the results show that as the concentration of graphene oxide increased the inhibition zone increased also against both types of bacteria. Whene the ratio of added graphene oxide was (15%) maximum inhibitionzone hase been calculated.Keywords: Graphene oxide; Nickle Phthalocyanine; Antimicrobial.